Ο Θεσμός του Μέντορα: Απόψεις Έμπειρων Εκπαιδευτικών για τις Προϋποθέσεις και τα Προσδοκώμενα Οφέλη - Μακροπούλου, Ελένη; Ιορδανίδης, Γεώργιος (Education Sciences, 2016)
This paper provides evidence on key participants in a future induction program of newly appointed teachers, their expectations from mentoring, and the factors affecting its successful implementation in Greek Secondary Education. Accordingly, mentoring by experienced teachers is approached as a rewarding learning experience with benefits affecting the whole educational system. It is also viewed as a highly demanding professional practice, which should be insured by overcoming barriers imposed by the educational system’s organisation and culture, implementing a reliable system for selecting and preparing potential mentors as well as evaluating the work offered by them.